Práticas verdes, de bem-estar social e animal voltadas à indústria de laticínios sob à ótica da responsabilidade social corporativa - Fin, Amanda Souza (2024)
The dairy industry plays a crucial role in job creation and food supply. This dissertation aimed to develop a framework for implementing corporate responsibility practices in the dairy industry, based on the pillars of green practices, social well-being, and animal welfare. Initially, a systematic literature review was conducted, followed by a diagnosis of responsible practices, through interviews with subjects from dairy industries located in Rio Grande do Sul and documentary research on companies' social networks. The need for formal policies to establish measurable goals was noted, and despite recognizing the importance of improving their actions, many organizations lack systematic approaches. In view of this, a framework to assist companies in implementing CSR was proposed, in which circular dynamics and adaptive strategies are suggested, as well as consideration of the forces that can influence, including the legal, sociocultural, natural environment, and connections with stakeholders.